COVID-19 threatens the developing world's small businesses. This is how to save them (2020)
The 23-year-old entrepreneur came fresh from the Smart Duka program, a partnership between TechnoServe and the Citi Foundation, where she had learned to keep business records, manage her stock, and treat her customers in such a way that they’d keep coming back.